CORRECTIVE FEEDBACK AND LEARNER AUTONOMY IN EFL WRITING - Hilman, Fathin Anjani (2017)
For the past decades, the concept of learner autonomy has been widely discussed and considered as an educational goal today as well as in Indonesian education context. A common problem for EFL teachers was dealing with passive classes, where students expect to be taught by their teacher instead of learning by themselves, especially in writing skill. Providing color-coded feedback in students' writing is one of the solutions in developing students' autonomy and improving the learning outcome. This study involved 90 students at English Education Department in UIN Bandung. The data were collected from students' writing drafts, interviews, questionnaires and self-reflection forms. After the data were qualitatively and quantitatively analyzed, it was found that color-coded feedback is effective in reducing the number of errors on three grammatical items (articles, prepositions, and past tense verbs). Moreover, the nine factors of learner autonomy in writing had strong influence in the use of color-coded feedback in students' writing, which lead to the development of students' autonomy. Further, students positively responses toward the use of color-coded feedback in their writing to develop their autonomy. As a conclusion, color-coded feedback is proven applicable in developing students' autonomy in writing. For further research, it is suggested that color-coded feedback can be used in developing learner autonomy in writing but it was seen that there is a need for a further detailed research on each category separately to understand the phenomenon better. Keywords: corrective feedback, color-coded feedback, writing, learner autonomy Beberapa dekade terakhir, konsep learner autonomy telah banyak dibahas dan dianggap sebagai tujuan pendidikan, begitu pula dalam konteks di Indonesia. Permasalahan umum bagi guru EFL adalah berurusan dengan kelas yang pasif, di mana siswa berharap untuk diajarkan oleh guru daripada belajar secara mandiri, terutama dalam pengajaran writing. Memberikan color-coded feedback dalam tulisan siswa merupakan salah satu solusi dalam mengembangkan kemampuan learner autonomy dan meningkatkan hasil belajar siswa. Penelitian ini melibatkan 90 siswa di Prodi Pendidikan Bahasa Inggris, UIN Bandung. Data dikumpulkan dari tulisan siswa, interview, questionnaire, dan self-reflection form. Data dianalisis secara kualitatif dan kuantitatif, kemudian ditemukan bahwa: Pertama, color-coded feedback efektif dalam mengurangi jumlah error di tiga kesalahan gramatikal (tata bahasa), yaitu article, verb, dan preposition. Kedua, sembilan faktor dalam learner autonomy memiliki pengaruh yang kuat dalam penggunaan color-coded feedback di tulisan siswa, yang mengarah ke perkembangan kemampuan learner autonomy. Ketiga, siswa memberikan respon yang positif terhadap penggunaan color-coded feedback dalam tulisan mereka untuk mengembangkan kemampuan learner autonomy. Sebagai kesimpulan, color-coded feedback dapat diaplikasikan terhadap perkembangan learner autonomy dalam keterampilan menulis siswa. Untuk penelitian selanjutnya, disarankan untuk lebih lanjut dalam setiap kategori untuk memahami fenomena lebih dalam. Kata kunci: corrective feedback, color-coded feedback, writing, learner autonomy